What happens when Islamic capital markets move away from tax neutrality – a look at Oman & Saudi Arabia - Selamat, A.; Syed Mohamed, Mohamed Ariff; Mohamad, Shamsher (Universiti Putra Malaysia Press, 2015)
This article evaluates how tax reforms affect stock prices of local and foreign firms in Oman and Saudi Arabia. Both countries introduced corporate tax on foreign firms, exempting local firms from corporate tax, when they moved away from a pre-existing Islamic tax neutrality policy. These reforms were implemented in 2009 in Oman and in 2004 in Saudi Arabia. These tax reform events – applying to foreign firms and not applying to local firms in the same markets – offer ideal experimental situations in two economies to test the taxation theories on how stock prices must react. We find that the results support the ModiglianiMiller and Elton-Gruber tax theories in two ways. Firstly, foreign firms that had their taxes reduced experienced stock price increases. Secondly, local firms not subjected to tax or tax reduction showed no visible tax effect. These are theory-consistent findings in the unique tax environments in these two Islamic countries, which moved away from tax neutrality, enabling us to obtain very clear evidence on modern theories of taxation. In our view, this evidence is significantly important addition to the literature on tax and taxation and for those contemplating a move away from Islamic tax neutrality.